2017
DOI: 10.1002/cae.21879
|View full text |Cite
|
Sign up to set email alerts
|

Development of an open experimentation tool based on JavaScript for the control of a four‐tank plant

Abstract: At present, one of the main problems which can be found within chemical engineering education is the availability of real industrial plants able to provide an experimentation framework. The importance of this kind of plants lies in allowing students to apply the learned theoretical concepts to solve real problems. In this paper, a remote tool for educational purposes is presented. More specifically, the implementation of a four‐tank plant, its internal control design and the implementation of an EasyJava tool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…e main contribution of this research is that the proposed DET focuses on learning the fundamentals, basic structure, and application of FLC with an innovative computing tool similar to those presented in [10,11], where students have at their provision of resources to carry out simulations of control systems, managing to break down barriers in the learning process such as the high cost of having access to real processes and the gap that students perceive between theoretical concepts and practice, as demonstrated in [12,13]. When making a comparison of the proposed DET with the research carried out in [20][21][22][23], the advantage that was found was that the developed DET has the visual integration of all the elements that make up an FLC, allowing for the understanding of the designers' effects of the modifications in the control system by modifying any parameter or variable that intervenes in the controller and system to be controlled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…e main contribution of this research is that the proposed DET focuses on learning the fundamentals, basic structure, and application of FLC with an innovative computing tool similar to those presented in [10,11], where students have at their provision of resources to carry out simulations of control systems, managing to break down barriers in the learning process such as the high cost of having access to real processes and the gap that students perceive between theoretical concepts and practice, as demonstrated in [12,13]. When making a comparison of the proposed DET with the research carried out in [20][21][22][23], the advantage that was found was that the developed DET has the visual integration of all the elements that make up an FLC, allowing for the understanding of the designers' effects of the modifications in the control system by modifying any parameter or variable that intervenes in the controller and system to be controlled.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main trends in the educational field is the development of computational tools that facilitate the improvement in the learning of engineering concepts [11]. ese tools can be remote laboratories such as those developed in [12,13], in which the problem of not having industrial processes to carry out practices in the engineering area was solved.…”
Section: Introductionmentioning
confidence: 99%